Failed Family Sagas: Male Lineage in Italian/American Literature and Literary Tradition - Pelayo-Sañudo, Eva (International Journal of English Studies, 2021)
The aim of this article is to examine how failed family sagas have defined early Italian/American culture and female literary tradition through Julia Savarese’s The Weak and the Strong (1952) and Marion Benasutti’s No Steady Job for Papa (1966). The idea of failed (female) lineages is articulated in a thematic sense that is overtly expressed in the depiction of both families in the texts. These convey a doomed plot which matches the coarse realities of immigration and the depression, as well as reflects the boundaries represented by the intersecting limitations of embodying racial and gender difference. Particularly, the article focuses on how male lineage is paramount in the novels and define Italian/American culture. In this sense, the analysis also contends that, as the authors themselves also encountered similar limitations, the lost genealogy of these early precursors has equally endangered the Italian/American female literary tradition.